Development of 3-D mathematical model of raceway size in blast furnace. (20th April 2016) - Li, Y. L.; Cheng, S. S.; Zhang, P.; Guo, J.
Abstract : A three-dimensional (3-D) mathematical model to predict raceway diameter has been developed based on previous 2-D studies. The results show that the 3-D simulated results on raceway diameter are in good agreement with measurements of two Chinese blast furnaces. Moreover, it is more precise than previous models. The effect of blast velocity, bed porosity and particle diameter has been investigated. An increase in gas velocity relative to a decrease in velocity leads to a larger downward frictional force so that the raceway diameter is smaller. A low bed porosity and a small particle diameter result in low normal pressure in the Cartesian region and low radial pressure in the radial region, which is not beneficial for smooth operation.